The Impact of Internal and External Factors on Student Entrepreneurial Resilience: The Mediating Role of Entrepreneurship Intention and Moderating Effect of Self-Efficacy - Firdaus, Muhamad Himami; Suryokumoro, Herman; Solimun; Hidayati, Bunga (Graduate School Universitas Brawijaya, 2025)
This study explores the impact of the Entrepreneurship Education Program on student entrepreneurial resilience, focusing on internal and external factors, the mediating role of entrepreneurial intention, and the moderating effect of self-efficacy. Utilizing quantitative methods and Structural Equation Modeling (SEM) with Smart PLS, data from 100 students at Universitas Brawijaya revealed significant positive relationships between entrepreneurship education and key indicators, including entrepreneurial interest, innovation capability, resilience, self-concept, and self-efficacy. Results highlight that effective entrepreneurship education enhances students' entrepreneurial attributes and emphasizes the critical role of self-efficacy in boosting entrepreneurial interest. Additionally, the supportive influence of the family environment underscores the importance of a comprehensive approach in fostering entrepreneurial skills. These findings align with existing literature and suggest that educational institutions should focus on both practical and theoretical aspects to prepare students for entrepreneurial success. Keywords: Entrepreneurship Education, Entrepreneurial Resilience, Self-efficacy, Innovation Capability, Entrepreneurial intention, Family Environment